Conceptual qualifying poor students digital business model: enhancing the B40 student & youth wellbeing through humanizing digital entrepreneurship education program - Lutf Al-Dailami, Edres Abdulwahab; Said, Abidina; Ahmad Dahlan, Abdul Rahman (Research publish, 2020)
This paper proposes a conceptual solution to help needy students to be qualified to enter the job market by providing them useful websites, applications, and facilities. Qualifying Poor students (QPS) is a business model that provides a digital platform to make students access many courses quickly. Moreover, QPS is also face to face learning to prepare students to communicate with lecturers to gain communication skills. The design thinking approach has been adopted in this paper to address the wellbeing issues of B40 students & youth in Malaysia through understanding their need, and then followed by building conceptual business models using modelling tools, such as Business Model Canvas (BMC) and Value Proposition Design Canvas (VPC). The approach includes conducting a literature review and interviews for understanding the needs, challenges, and critical problems, formulating and ideating initial business model options in solving the issues, and validation of the initial business model by interviewing the various customer segments, which are the donors, students, teachers, adult workers, companies and government employees.